Ion processing of zirconium ceramics by high-power pulsed beams - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Vasiljev I. P. Ivan Petrovich; Surzhikov A. P. Anatoly Petrovich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Chernyavski (Chernyavskiy) A. V. Aleksandr Viktorovich (2015, 2015)
Title screen